2010
DOI: 10.1590/s1726-46342010000300022
|View full text |Cite
|
Sign up to set email alerts
|

Probable transmisión vertical del virus de la influenza A (H1N1): a propósito de un caso

Abstract: We report the case of a male newborn, product of a 36 week pregnancy, with diagnosis of congenital pneumonia and with a confirmatory test for influenza A (H1N1) virus, without any other suspicious contact. The mother was admitted to the hospital with respiratory failure and the history of a flu-like episode of 5 days of evolution, during the first days of the pandemic in Peru. Due to the severe evolution of the respiratory process, assisted ventilation was given to her and then a cesarean section was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…93 During the 2009 H1N1 (swine flu) pandemic an estimated 11 to 21% (700 million to 1.4 billion people) of the world population became infected, and there were 4 case reports of suspected H1N1 vertical transmission in newborns of infected mothers. [94][95][96][97] All 4 infants were delivered by cesarean section, had severely ill mothers positive for H1N1, and were tested immediately after birth, prior to contact with the mother. An infant born at 36 weeks tested positive for H1N1 after his mother had respiratory failure and required assisted ventilation.…”
Section: Influenzamentioning
confidence: 99%
See 2 more Smart Citations
“…93 During the 2009 H1N1 (swine flu) pandemic an estimated 11 to 21% (700 million to 1.4 billion people) of the world population became infected, and there were 4 case reports of suspected H1N1 vertical transmission in newborns of infected mothers. [94][95][96][97] All 4 infants were delivered by cesarean section, had severely ill mothers positive for H1N1, and were tested immediately after birth, prior to contact with the mother. An infant born at 36 weeks tested positive for H1N1 after his mother had respiratory failure and required assisted ventilation.…”
Section: Influenzamentioning
confidence: 99%
“…An infant born at 36 weeks tested positive for H1N1 after his mother had respiratory failure and required assisted ventilation. 94 A preterm newborn was born at 31 weeks with postnatal findings of respiratory distress and tested positive for H1N1; her mother had cardiopulmonary failure and died on day 7. 95 In the third report, a full-term newborn had a throat swab positive by rtPCR for H1N1 after developing respiratory distress requiring ventilatory support on day 1; her mother had respiratory distress and required ventilatory support for 14 days.…”
Section: Influenzamentioning
confidence: 99%
See 1 more Smart Citation
“…There are four reports of suspected H1N1/09 vertical transmission in newborns whose mothers were infected [10]. Vasquez et al reported a case of a premature baby boy delivered by cesarean section due to fetal distress [21]. The mother was infected with H1N1 during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The mother was infected with H1N1 during pregnancy. The newborn, who had no contact with the mother after birth, was subsequently identified as being infected with the H1N1 influenza virus [21]; however, the placenta was not tested for virology and pathology, so direct evidence of vertical transmission was lacking. Similar reports have been made in Thailand [22], India [23] and Turkey [12].…”
Section: Discussionmentioning
confidence: 99%